Developing English Learning Media Through Digital-Based to Improve Students’ Vocabulary - Nanda Febriana (Journal of Research Education and English Teaching, 2025)
To be able to master the four English language skills require mastery of a lot of vocabulary, vocabulary is the most important part in a language, one of which is English. This study aims to develop and produce digital-based learning media to improve students’ English vocabulary and to determine students’ perceptions of learning media that are developed. The type of research method in this study is R&D (Research and Development) method with 4D development model which is then simplified into 3D (define, design, and development). The subject of this study were students of Class VII SMP Negeri 5 Campalagian which amounted to 24 students. The instruments used in this study were interviews and questionnaires used to test the feasibility of the product and determine the perception of students. The results obtained in this study are (1) Digital-based learning media made in the form of android applications to improve students’ English vocabulary and named is LEV (Learning English Vocabulary). Learning media has gone through 3 stages of development namely define, design, and development and has been tested for feasibility by 2 experts, namely media experts and material experts. (2) learning media is stated to be interesting based on the results of the questionnaire analysis of students perceptions of the developed media that is 100% and based on the results of interviews conducted by researcher on 10 students regarding their comments on the developed media that they provide positive comments on the learning media.